Pre-Sowing Treatments Accelerate Germination Percent for Restoration of Fourteen Threatened Tree Species in Bangladesh - Hasnat, G.N.T.; Hossain, M.A.; Hossain, M.K. (Department of Forestry and Environmental Science University of Sri Jayewardenepura, 2019)
Ecologically valuable native tree species are becoming threatened due to deforestation, forest fragmentation and preference of fast-growing exotics than the native ones in plantation. One of the main reasons for the preference of exotic species than the native ones is its higher rate of germination and rapid growth. The effect of different pre-sowing treatments was studied on fourteen threatened tree species of Bangladesh to find out the appropriate treatments for speed up germination rate and initial seedling growth. These species are ecologically valuable multipurpose indigenous trees of Bangladesh. Methanol extract of Castanopsis indica leaves could decrease the tumor Ehrlich Ascites Carcinoma volume and weight. Lophopetalum wightianum is a globally threatened tree species. Hard coated seeds of Canarium resiniferum, Castanopsis indica, Protium serratum, Quercus acuminata and Vitex peduncularis were treated with sand paper, nicking, normal water, hot water, H2SO4 and HCl. Soft coated seeds of Brownlowia elata, Dichopsis polyantha, Firmiana colorata, Lophopetalum wightianum, Pterospermum acerifolium, Pterospermum semisagittatum, Pterygota alata, Schleichera oleosa and Sterculia villosa were sown in polybags, propagator house and nursery bed in normal, flat and 45o angle positions. Among all hard-coated seeds, Castanopsis indica showed significantly higher germination percentage (67%) after seeds treated with sandpaper in comparison to control (25%). Soft-coated seeds of Lophopetalum wightianum showed significantly higher germination percentage (90%) among all studied species when sown in propagator house, whereas in natural condition it provides only 26% germination rate. This paper will help to restore ecologically valuable threatened species.
Keywords: Pre-sowing treatment, globally and nationally threatened tree species, germination rate, hard or soft-coated seed, Bangladesh